Effect of Gamma Ray Irradiation on Structural and Optical Properties of ZnO Thin Films - K. H. Al-Maiyaly, Bushra (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research, the structural and optical measurements were made on the Zinc oxide (ZnO) films prepared by two methods once by using chemical spray pyrolysis technique, and another by using thermal evaporation technique before and after irradiation by Gamma –Ray (γ – rays) from source type (Cs 137) with an energy (0.611)MeV as a function of gamma dose (0.15,0.3 and 0.45) Gy. The thickness of all films prepared by two method was about (300 ± 50) nm. XRD is used to characterize the structural properties, the results demonstrated that all samples prepared by two method before and after irradiation have polycrystalline structure with a preferred orientation (002).Also it showed that the structural properties are weakly dependent on the gamma dose. The optical measurement shows that all ZnO films prepared by two method have a direct energy gap, and they in general decrease with the increase of Gamma dose while the optical constant such as absorption coefficient, refractive index, extinction coefficient, real and imaginary parts of the dielectric constant and optical conductivity showed an opposite trend, these values increase with the increase of irradiation dose. As well as all optical properties for the samples prepared by thermal evaporation technique is higher than the samples prepared by chemical spray pyrolysis technique.